Vpliv fluvoksamina in maprotilina na sproščanje in farmakokinetiko histamina pri podgani in vivo - Jug, Borut (Medicinski razgledi, 1998)
Antidepressants are known to influence the kinetics of histamine. The purpose of this study was twofold: to determine the influence of various doses of antidepressants fluvoxamine and maprotiline on induced histamine Iiberation and its further elimination and to find out whether histamine elimination is influenced by its redistribution from plasma to blood. Rats (n = 24) were pre-treated with two doses of antidepressant at an interval of 24 hours. One hour after the administration of the second dose of antidepressants, the rats received histamine liberator-compound 48/80 (0.05 microg/g) or exogenous histmine (10 mocrog/g). Blood samples were taken from the carotid artery at 5 and 15 minutes afler fhe injection of the histamine liberator-for measurementsof plasma histamine levels, and at 2 minutes afler the injection of exogenous histamine-for separate determinations of plasma and blood histamine levels. Afler a two-step purification procedure, histamine levels were measured by spectrofluorometry. Both antidepressants inhibited the rise of plasma histamine because of the effects of compound 48/80. The study animals showed significantly higher values of elimination constants than controls. It is assumed that antidepressants inhibit histamine liberation and promote its elimination. Rats pre-treated with antidepressants had lower plasma and blood histamine levels after exogenous histamine injection than control animals, while their plasma histamine/blood histamine ratio did not change signiflcantly. We suppose that accelerated elimination of histamine is not the resuft of its redistribution from plasma to blood and blood elements but is rather the consequence of increased metabolism of histamine and/or its binding in other tissues.
Keywords: drug; Histamine; zdravila; Pharmacokinetics; farmakodinamika; Histamine release; histamin; Drug effects; podgane; Antidepressive agents; Pharmacology; Rats, wistar; Fluvoxamine; Maprotiline; Receptors, histamine